The Dynamic of the Interaction between the Modern Medical System and the Traditional Medical System: Finding a Way for Establishing a Harmonious Collaboration of the Two Systems for the Social Justice for the People - Meutia Farida Swasono; Rhino Ariefiansyah (Antropologi Indonesia, 2020)
The special edition of Medical Anthropology of the Journal Antropologi Indonesia consist of selected articles which has been presented in the International Symposium of the journal Antropologi Indonesia (ISJAI), held in Jogyakarta on July 23-26, 2019, at the Gadjah Mada University. The International Symposium is a collaboration between the Department of Anthropology of the University of Indonesia and the Department of Anthropology of the Gadjah Mada University.